(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article indicates a focus on language transfer, specifically exploring its types. Understanding positive transfer’s benefits and addressing challenges like negative transfer, interference, overgeneralization, and fossilization is essential in language teaching.